Capsule Endoscopy Validation of the Magnetic Enterography Global Score in Patients with Established Crohn's Disease. (10th January 2018) - Klang, Eyal; Amitai, Marianne M; Lahat, Adi; Yablecovitch, Doron; Avidan, Benjamin; Neuman, Sandra; Levhar, Nina; Rozendorn, Noa; Weiss, Batya; Ben-Horin, Shomron; Eliakim, Rami; Kopylov, Uri; et al.
Abstract: Background and Aims: Capsule endoscopy [CE] and magnetic resonance enterography [MRE] are prime modalities for evaluation of the small bowel in Crohn's disease [CD]. Detection of proximal small bowel [SB] inflammation in CD by MRE is challenging. Currently available quantitative MRE scores do not incorporate proximal SB data. The MRE global score [MEGS] was designed for quantitative evaluation of the entire digestive tract; its accuracy in the proximal SB has not previously been evaluated. This study compared the evaluation of the small bowel inflammation by MEGS and CE-derived quantitative score (the Lewis score[LS]). Methods: CD patients in stable clinical remission were prospectively recruited and underwent MRE and CE; faecal calprotectin [FC] levels were obtained. MEGS was calculated for each SB segment and the entire SB [SBMEGS]. SB inflammation on CE was quantified using LS. A cumulative Lewis score [C-LS] was calculated based on summation of three tertiles scores. Results: Fifty patients were included. There was a significant correlation of SBMEGS with LS and C-LS [ r = 0.61 and 0.71, both p = 0.001]. The correlation with FC was stronger for MEGS than for LS or C-LS [ r = 0.68 vs r = 0.46 vs r = 0.53, all p = 0.001]. The correlation between the proximal LS and MEGS was significant [ r = 0.55, p = 0.001]; median MEGS was significantly different in patients, with LS values consistent with mucosal healing, mild and moderate-to-severe inflammation. Conclusions: MEGS provides accurate evaluation of the SB and strongly correlates with FC; the main advantage of MEGS is the accurate quantification of proximal SB inflammation unavailable for alternative MRE scores.